2012
DOI: 10.1016/s1674-8301(12)60002-5
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania donovani whole cell antigen delivered with adjuvants protects against visceral leishmaniasis in vervet monkeys (Chlorocebus aethiops)

Abstract: In a previous immunogenicity and efficacy study in mice, montanide ISA 720 (MISA) was indicated to be a better adjuvant than bacillus calmette guerin vaccine (BCG) for a Leishmania vaccine. In the present study, we report the safety, immunogenicity and efficacy of Leishmania donovani (L. donovani) sonicated antigen delivered with alum-BCG (AlBCG), MISA or monophosphoryl lipid A (MPLA) in vervet monkeys following intradermal inoculums. Vaccinated and control animals were challenged with virulent L. donovani par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
1
22
0
1
Order By: Relevance
“…Two weeks following the last day of treatment, all infected mice were sacrificed and parasite numbers were determined microscopically by counting the number of amastigotes in Giemsa stained splenic impression smears. Amastigote burdens were compared for both experimental and control groups and results expressed as the number of amastigotes per 500 splenic cell nuclei as described before [12] .…”
Section: Methodsmentioning
confidence: 99%
“…Two weeks following the last day of treatment, all infected mice were sacrificed and parasite numbers were determined microscopically by counting the number of amastigotes in Giemsa stained splenic impression smears. Amastigote burdens were compared for both experimental and control groups and results expressed as the number of amastigotes per 500 splenic cell nuclei as described before [12] .…”
Section: Methodsmentioning
confidence: 99%
“…However, the study indicated adverse reactions following immunization with BCG vaccine. More recently, these murine data were evaluated in the vervet monkey model of visceral L. donovani leishmaniasis, where animals were vaccinated with L. donovani whole sonicate antigen with or without alum-BCG, monophosphoryl lipid A or MISA 720[55]. The results indicated strong type 1 immune responses in animal groups immunized with either alum-BCG+Ag or MISA+Ag, with the MISA+Ag vaccinated animals having better results than the alum-BCG+Ag group.…”
Section: Development Of Leishmania Vaccinesmentioning
confidence: 99%
“…Each vaccine formulation was prepared by mixing 0.1 mg of the purified recombinant protein and Montanide ISA 720 VG in 7:3 proportion [18,19]. The mixtures were vortexed for 1 min and incubated at 4°C for 24 h. The vaccine formulations (0.1 ml) were inoculated on Luria agar plates and incubated at 37°C for 24 h to verify their sterility.…”
Section: Preparation Of the Vaccine Formulations And Immunizationmentioning
confidence: 99%